2012
DOI: 10.1371/journal.pbio.1001255
|View full text |Cite
|
Sign up to set email alerts
|

Development and Function of Invariant Natural Killer T Cells Producing TH2- and TH17-Cytokines

Abstract: Four distinct subsets of invariant natural killer T (NKT) cells are shown to differentiate in the thymus, then migrate to peripheral tissues where they retain their phenotypic and functional characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
224
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(236 citation statements)
references
References 59 publications
12
224
0
Order By: Relevance
“…[12][13][14] More recently, several investigators have proposed three iNKT sublineages based on thymic development and distinct functions. [14][15][16][17][18] These sublineages include NKT1 cells, which have high expression of the T-box transcription factor T-bet (Th1-like iNKT cells) and secrete large amounts of IFN-c upon stimulation; NKT2 cells highly express GATA-binding protein 3 (GATA-3) (Th2-like iNKT cells) and produce IL-4 upon stimulation, whereas NKT-17 cells (Th17-like iNKT cells) express high levels of retinoic acid receptor-related orphan receptor-ct (RORct) and produce IL-17 under activated conditions. 17 The above description raises the possibility that the function of specific iNKT cell sublineages may be determined by transcriptional programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] More recently, several investigators have proposed three iNKT sublineages based on thymic development and distinct functions. [14][15][16][17][18] These sublineages include NKT1 cells, which have high expression of the T-box transcription factor T-bet (Th1-like iNKT cells) and secrete large amounts of IFN-c upon stimulation; NKT2 cells highly express GATA-binding protein 3 (GATA-3) (Th2-like iNKT cells) and produce IL-4 upon stimulation, whereas NKT-17 cells (Th17-like iNKT cells) express high levels of retinoic acid receptor-related orphan receptor-ct (RORct) and produce IL-17 under activated conditions. 17 The above description raises the possibility that the function of specific iNKT cell sublineages may be determined by transcriptional programs.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] These sublineages include NKT1 cells, which have high expression of the T-box transcription factor T-bet (Th1-like iNKT cells) and secrete large amounts of IFN-c upon stimulation; NKT2 cells highly express GATA-binding protein 3 (GATA-3) (Th2-like iNKT cells) and produce IL-4 upon stimulation, whereas NKT-17 cells (Th17-like iNKT cells) express high levels of retinoic acid receptor-related orphan receptor-ct (RORct) and produce IL-17 under activated conditions. 17 The above description raises the possibility that the function of specific iNKT cell sublineages may be determined by transcriptional programs. 19 During iNKT cell development, several transcription factors are involved in regulating phenotype and function, including a BTB-ZF promyelocyticzinc finger transcription regulator, which is specifically expressed in iNKT cells.…”
Section: Introductionmentioning
confidence: 99%
“…Three subsets of iNKT cells, referred to as iNKT1, iNKT2, and iNKT17, have recently been identified according to differential expression of PLZF, T-bet, IL-17RB, and Rorγt, and distinct cytokine profiles (10,12). Analysis of spleen and lymph node cells revealed that the number of all three iNKT subsets was reduced in Fnip1 −/− mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to NK cells [52], slp-76 ace/ace iNKT cells more frequently expressed NK-cell receptors (especially NK1.1, NKG2D, and Ly49G2) and CD122 than their B6 counterparts (Supporting Information Table 1). In contrast, IL-17RB, which is predominantly expressed on NKT2 and NKT17 cells [18], was selectively reduced (Supporting Information ADAP −/− mice exhibited no significant differences in the expression of any of these markers compared to control mice (data not shown). Although based on these observations the slp-76 ace/ace mutation was expected to favor a Th1-polarization, iNKT cells from slp-76 ace/ace mice released less IL-4, and IFN-γ upon stimulation with α-GalCer compared to WT cells, i.e.…”
mentioning
confidence: 99%
“…Th2-or Th-17-polarized iNKT cells maintain their PLZF-expression at high or intermediate levels, respectively, and are primarily recovered from the lungs and peripheral lymph nodes [8,12,15]. Both subsets frequently express IL-17RB [18] and NP-1 which characterizes iNKT cells that recently emigrated from the thymus [19]. However, the role of NP-1 in iNKT cell biology has remained undefined.…”
mentioning
confidence: 99%